Vaginal Extrusion of Transobturator Tape 6 Years after Procedure: How Long Should Be the Follow-Up Period after Vaginal Sling Surgeries?. (26th November 2012) - Singh, Chanchal; Weng, Roy Ng Kwok
Abstract : A 77-year-old lady presented to the gynaecology outpatient clinic with vaginal extrusion (3C/T3/S1) six years after a transobturator suburethral sling procedure (TOT). The entire tape was spontaneously extruded vaginally and the vaginal erosion healed with conservative management. Midurethral tapes, currently the standard of care in the management of urodynamic stress incontinence (USI), are associated with a risk of erosion and extrusion of the synthetic material. The present case highlights the importance of the long-term followup after any sling procedure as erosion and/or extrusion may arise at any time following the procedure.